Investigating the academic writing potentials of freshmen at the University of Buea: Making a case for grammatical and lexical awareness - Nsen, Gisela Achuo (Research Journal in Advanced Humanities, 2021)
This study hypothesized “that one who has nothing to say has nothing to write” to investigate the effects of grammatical awareness on performance in language proficiency test among first-year university students at the University of Buea (UB). The sample comprised 100 first-year students purposively sampled from Use of English classes at UB. Using Piaget’s (1936) Theory of Cognitive Development, data for the study was collected and analysed using descriptive statistics. The findings revealed that pre-university students upon enrolment harbour stereotyped and somewhat erroneous forms and structures of grammar that eventually become difficult to get out of their minds, and these are often introduced by their teachers or sometimes the environment they come from. Based on the findings, the study recommends that teachers of English at every stage should endeavour to engage students with real-life language use as this has the potentials to improve the communicative abilities.